French Sign Language/French Translation Studies in France: A Mini Review - Burgat, Sandrine; Encrevé, Florence; Segouat, Jérémie (Frontiers in Communication, 2022)
In this mini review, we present an overview of existing research in French sign language (LSF)/French translation studies in France. The practice of LSF/French interpreting is ancient, since traces of it can be found in the High Middle Ages, but its professionalization is more recent (it dates from the Deaf Revival of 1975-1995). The profession of French to LSF translator is even more recent: it dates from about ten years ago. Following this professionalization, translation studies research emerged about thirty years ago. It has been developing particularly over the last twenty years, driven by university programs (MA in LSF/French interpretation and translation). This research is multifaceted and is not confined to a single discipline. Indeed, translation studies are inherently multidisciplinary, and we can find references to translation and interpretation in historic, linguistic, sociologic, or computer science studies, among others. Moreover, translation studies are also part of different schools of thought, which can be explained historically. In this paper, we present an overview of translation research concerning LSF/French interpretation and translation (practiced by both deaf and hearing people) in France. We also address the prospects for further developments, related to the emergence of new practices, and the question of the didactic applications of these different researches in the field of interpreters and translators training within 5 universities in France.